Influenza vaccines: 'tailor-made' or 'one fits all'. (August 2018) - Saletti, Giulietta; Gerlach, Thomas; Rimmelzwaan, Guus F
Highlights: Inactivated vaccines induce protective antibodies against antigenically matching strains. There is an unmet need for 'one fits all' influenza vaccines. These should induce antibody and T cell responses to conserved epitopes. Potential vaccine targets are HA stalk, NA, M2e and internal proteins. Abstract : Currently used inactivated influenza vaccines aim at the induction of virus-neutralizing antibodies directed to the variable head domain of the viral hemagglutinin. Although these vaccines are effective against antigenically matching virus strains, they offer little protection against antigenically distinct drift variants or potentially pandemic viruses of alternative subtypes. In the last decades, the threat of novel influenza pandemics has sparked research efforts to develop vaccines that induce more broadly protective immunity. Here, we discuss the immune responses induced by conventional 'tailor-made' inactivated and live influenza vaccines and novel 'one fits all' candidate vaccines able to induce cross-reactive virus-specific antibody and T cell responses and to afford protection to a wider range of influenza viruses.